(Non-)Dependence and (Non-)Safety of Nursing Work in the Context of Pandemic: Modern Empirical Approaches - Natalia Sergeevna Baisha (Интеракция. Интервью. Интерпретация)
The article is devoted to nursing work, which is realized in (not)favorable and (not)safe conditions, (not)aggravating the emotional and physical condition of its representatives. Using some ideas of the neo-Weberian approach and focusing on the pandemic crisis as an event that exposed the insecurity of nursing practice, various variations of improvement, including by nurses themselves, of their working conditions will be considered. The main objective of the article is to summarize the existing ideas about nursing everyday life during the COVID-19 pandemic on the basis of foreign studies published in one of the authoritative journals devoted to the study of nursing communities. Based on the materials of foreign studies, the working conditions of nurses are presented and described, ways of overcoming pandemic-related difficulties encountered in daily nursing practice are identified, including self-organization and freedom of timely decision-making by nursing staff. It is shown that the recognition by the management and medical corps of the role of nurses in overcoming the pandemic crisis, giving them the opportunity to be heard, influence changes in working conditions and take part in risk management, can positively affect their emotional and physical conditions, as well as reduce the number of real threats that disorganize nursing work and the quality of patient care. The article contributes to the study of nursing work during the pandemic and gives an idea of some areas of foreign research, the development of which is also important within the framework of Russian research practice.